2015
DOI: 10.1590/0102-37722015021882193201
|View full text |Cite
|
Sign up to set email alerts
|

Contribuições de uma Intervenção Psicoeducativa para o Enfrentamento do HIV durante a Gestação

Abstract: RESUMO -O estudo investigou as contribuições de uma intervenção psicoeducativa para o enfrentamento da doença entre gestantes vivendo com HIV. Participaram quatro mães com idades entre 29 e 37 anos, sendo que duas souberam da infecção na gestação. Trata-se de estudos de casos longitudinal envolvendo avaliações antes, durante, depois da intervenção e aos três meses de vida do filho/a. Os achados revelaram que a notícia do HIV durante a gestação se associou a grande risco psicológico, pois envolvia imenso esforç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
4
0
1
Order By: Relevance
“…When it comes to the HIV diagnosis, it should be remembered that HIV seropositivity has been fraught with stigma and prejudices since the beginning of the epidemic, constituting some of the factors which allow concealment of diagnosis in the social sphere of the individual. Studies have shown that the fact that the disease constitutes a taboo for several social groups forces people to face psychosocial and emotional challenges which interfere in the disclosure and diagnosis acceptance process, thereby opting for confidentiality (21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the HIV diagnosis, it should be remembered that HIV seropositivity has been fraught with stigma and prejudices since the beginning of the epidemic, constituting some of the factors which allow concealment of diagnosis in the social sphere of the individual. Studies have shown that the fact that the disease constitutes a taboo for several social groups forces people to face psychosocial and emotional challenges which interfere in the disclosure and diagnosis acceptance process, thereby opting for confidentiality (21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, women often feel physically overloaded, refers to more pain, which can restrict mobility and routine activities at the end of pregnancy (Olsson and Nilsson-Wikmar, 2004). The context of HIV adds an extra burden to this scenario, bringing concerns related to navigate the MTCT recommendations to prevention (Ashaba et al, 2017b; D’Auria et al, 2006; Gonçalves and Piccinini, 2015). Despite more frequent healthcare visits, MLWH can still feel a lack of information and support due the complexity and demanding context of pregnancy and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal care involves more visits, examinations, and medication than regular care (Brasil/ MS, 2018), which is usually associated with the limited socioeconomic resources of the families in Brazil, contributing to women's fatigue. In addition, in Brazil, these mothers intensely worry about potential HIV disclosure situations, such as not being able to breastfeed (Gonçalves and Piccinini, 2015). In order to avoid HIV disclosure, mothers often take over the care of the newborn and administration of the medication on their own (D'Auria et al, 2006;Faria and Piccinini, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Devido ao risco elevado de complicações nutricionais, a intervenção baseada nos dados recolhidos por uma avaliação completa, deverá ocorrer logo após o diagnóstico de infecção pelo vírus. Por outro lado, é importante salientar que o seguimento, tal como a avaliação nutricional, são Research, Society and Development, v. 10, n. 7, e4510716378, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i7.16378 procedimentos essenciais para que haja uma ótima prestação de cuidados por parte do nutricionista (Oliveira, Leite & Claro, 2015;Gonçalves & Piccinini, 2015).…”
Section: Os Benefícios Da Nutrição Adequada Em Pacientes Portadores Do Vírus Da Imunodeficiência Humana (Hiv)unclassified